2003
DOI: 10.1099/mic.0.26320-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of S-formylglutathione hydrolase in C1 metabolism of the methylotrophic yeast Candida boidinii

Abstract: The methylotrophic yeast Candida boidinii exhibits S-formylglutathione hydrolase activity (FGH, EC 3.1.2.12), which is involved in the glutathione-dependent formaldehyde oxidation pathway during growth on methanol as the sole carbon source. The structural gene, FGH1, was cloned from C. boidinii, and its predicted amino acid sequence showed more than 60 % similarity to those of FGHs from Paracoccus denitrificans and Saccharomyces cerevisiae, and human esterase D. FGH from C. boidinii contained a C-terminal trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…This observation seems to reflect the fact that the high-energy bonds of fatty acid thioesters are stabilized in peroxisomes during ␤-oxidation. On the other hand, during methanol metabolism, the reduced glutathione within peroxisomes is consumed through two critical reactions for methanol metabolism, i.e., by forming hydroxymethyl glutathione nonenzymatically and by being further oxidized to S-formylglutathione to metabolize formaldehyde (39) or by Pmp20-glutathione peroxidase to detoxify intraperoxisomal ROS (9).…”
Section: Discussionmentioning
confidence: 99%
“…This observation seems to reflect the fact that the high-energy bonds of fatty acid thioesters are stabilized in peroxisomes during ␤-oxidation. On the other hand, during methanol metabolism, the reduced glutathione within peroxisomes is consumed through two critical reactions for methanol metabolism, i.e., by forming hydroxymethyl glutathione nonenzymatically and by being further oxidized to S-formylglutathione to metabolize formaldehyde (39) or by Pmp20-glutathione peroxidase to detoxify intraperoxisomal ROS (9).…”
Section: Discussionmentioning
confidence: 99%
“…Esterase D, originally identified as a carboxyesterase in man with high activity toward 4-methylumbelliferyl acetate (MUA), was subsequently shown to be S-formylglutathione hydrolase (SFGH, EC 3.1.1.56), an enzyme catalysing the hydrolysis of S-formylglutathione to formic acid and glutathione. 4 SFGH is part of a pathway of formaldehyde detoxification conserved in prokaryotes and eukaryotes, 5 with the enzyme functionally characterised in Paracoccus denitrificans, 6 Saccharomyces cerevisiae, 7 Candida boidinii, 8 Escherichia coli 9 and A. thaliana. 10,11 Searches for homologues in other genome and EST databases show remarkable conservation in the sequence of SFGHs.…”
Section: Introductionmentioning
confidence: 99%
“…S-Formyl glutathione hydrolase is regulated by carbon and nitrogen source and is involved in the glutathione-dependent formaldehyde oxidation pathway. Its products can be used as carbon sources for growth (Yurimoto et al, 2003). Our results showed that the expression of S-formyl glutathione hydrolase in the mycelia was down-regulated under low nitrogen stress, suggesting that M. oryzae enhanced nitrogen metabolism in the mycelia and improved the synthetic ability of the desired carbon and nitrogen in order to ameliorate the adaptability of strains to adverse environmental conditions of nitrogen deficiency.…”
Section: Discussionmentioning
confidence: 80%